Oral health is impaired in Behcet's disease and is associated with disease severity - MUMCU, GONCA; DİRESKENELİ, RAFİ HANER; ERGUN, SAFİYE ATLAS TÜLİN (OXFORD UNIV PRESS, 2004)
Objectives. This study aimed to investigate the oral health of Turkish patients with Behcet's disease (BD) and whether it is associated with the disease course. Methods. One hundred and twenty patients with BD, 35 patients with recurrent aphthous stomatitis (RAS) and 65 healthy Turkish controls (HC) were included in the study. Oral health was investigated by indices applied in a BD out-patient clinic. Results. The mean scores of plaque, sulcus bleeding and gingival indices, probing depth and the number of extracted teeth were observed to be higher in patients with BD and RAS compared to HC (P<0.05). In the linear regression analysis, plaque index score was associated with the presence of oral ulcers and male gender. An elevated plaque index score was observed to be a significant risk factor for increased severity score in patients with BD in the logistic regression analysis (P = 0.034). Conclusions. Oral health is impaired in BD and associated with disease severity. Improvement of the oral health of BD patients may affect their disease course, leading to a better prognosis.
Keywords: oral ulceration; oral health; Behcet's disease; severity score; STREPTOCOCCUS-SANGUIS; DIAGNOSIS; SYMPTOMS; CRITERIA; ANTIGEN